Plastic photovoltaic roof tiles - Donkin, Richard Philip (Stellenbosch : University of Stellenbosch, 2010)
Thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Renewable and Sustainable Energy at the Stellenbosch University.